Germany's Energiewende at a Crossroads. Issue 2 (1st June 2021) - Heering, Jonas; Gustafson, Thane
Abstract: This article examines Germany's current climate and energy policies. Nearly two decades on, Germany's Energiewende —the transition to a less carbon-intensive economy—is at a crossroads. While remarkable advances have been made, the technical difficulties of expanding the energy transition beyond the electricity sector, the mounting costs of the transition itself, and now the covid -19 pandemic are slowing further progress. Maintaining the momentum of the Energiewende would require collaborative action, yet the principal political players have different agendas, making it difficult to reach decisions. In this article, we consider three of those actors: the German public, the opposition parties, and the government. We find that agreements on German climate policy have been diluted in political compromises and that real progress is being blocked. These problems will only increase as Germany deals with the consequences of the pandemic and faces a transition in national leadership in 2021.